Characterization of zirconium oxidecoating stabilized with cerium and yttrium oxide deposited on the bonding coating nickel chromium aluminum cobalt yttrium oxide - Mihailo Mrdak; Časlav Lačnjevac; Darko Bajić (Zaštita Materijala)
Zirconium dioxide ZrO2 is used as a basic material for thermal barriers and as a biomaterial for manufacturing parts for hip implants in orthopedic surgery and in dentistry for making crowns. Use of ZrO2 ceramics as an insulating material and biomaterial is due to its good chemical and dimensional stability, mechanical strength, toughness and elastic modulus. The aim of this study was to analyze the characteristics of zirconium oxide coating of stabilized cerium and yttrium oxide deposited by atmospheric plasma spraying (APS) process on the bond coating of nickel chromium cobalt yttrium oxide. Coatings were deposited on cold substrates and on substrates preheated to 180°C. Composite powder nickel chromium/aluminum/cobalt/yttrium oxide was used for the production of bond layers and for the ceramic layers zirconium oxide stabilized with cerium and yttrium oxide powder. Testing the quality of coatings was done by measuring microhardness of layers using the HV method and for bond tensile strength of the coating system tensile testing was applied. Metallographic evaluation of the share of pores in the bond and ceramic layers was performed with image analysis - processing of images from a light microscope. Powder particle morphology and EDS analysis were performed on the SEM. The obtained results confirm that the preheating temperature of the substrate has a significant impact on structural mechanical properties of the tested coatings system.